Experimental research into the process of biological treatment of wastewater with the use of the membrane bioreactor - Shevchenko, Tamara; Chub, Irina; Didrikh, Dmitry (Eastern-European Journal of Enterprise Technologies, 2018)
Effectiveness of operation of the membrane bioreactor (MBR) for wastewater treatment with the use of the biological method was considered. The pilot studies were carried out in the test membrane bioreactor, manufactured by company "Alfa Laval" (Denmark). The process of biological treatment of wastewater using the membrane bioreactor makes it possible to intensify the operation of biological treatment plants due to the lack of facilities for settling the sewers, an increase in the dose of active sludge up to 12–13 g/l; the process of deposition is replaced with filtration, washing of membrane modules can be carried out without emptying the tanks and without taking modules out of the tanks. In the process of testing of the membrane bioreactor, based on the module plant, manufactured by company "Alfa Laval" (Denmark) for treatment of domestic wastewater, the treatment mode that meets the requirements for discharge was achieved. Treatment effectiveness by basic indicators was: COD – 93 %, BOD5 – 99 %, suspended substances – 98.5 %, ammonium nitrogen – 98.5%. Operation efficiency of MBR as for nitrates amounted to 89 % after adjustment of reagent’s dose (40–50 mg/l) and the oxygen dose in the nitrification zone (2–3 mg/l). Efficiency of 98.6% for phosphates was achieved after the introduction of the reagent aluminum sulfate with the dosage of 40–50 mg/l. The study conducted has made it possible to obtain the consistent operation mode of the MBR with ensuring effective process of wastewater treatment. Dependences of wastewater treatment efficiency on the MBR as for major contaminants (COD, BOD5, nitrogen compounds and phosphorus) were shown. This enables meeting the strict requirements for wastewater discharge into water bodies and decreasing the cost value of the treatment through a decrease in power consumption. The mechanism of the MBR operation under conditions of treatment of actual wastewater, which allows determining the conditions of the use of the MBR in the technology of the biological wastewater treatment was studied.